Analysis of the Vegetative Characteristics of Four Varieties of Cowpea (Vigna Unguiculata) Grown in Two Seasons in the Province of Maniema (D.R. Congo) - MWISSA MUSOKE, Venant; MOKE LUKUSA, Bopole; BONONGA OKANI, Juré; ALIANGO UVON, Blaise; PALUKU NZIABAKI, Augustin; NGAMA BOLOY, Faustin; DHED’A DJAILO, Benoit; YENGA BOMBEKU, Dimanche (European Journal of Science, Innovation and Technology, 2026)
Cowpea (Vigna unguiculata) is a dietary legume of great importance for food security and nutrition in several parts of Africa. In the Maniema Province of the Democratic Republic of Congo, this crop is widely practiced by local farmers, but information on the morphological variability of these varieties under the same environment and during the different seasons is very limited. A situation that hinders the efficient use (cultivation) of varieties of this crop, particularly in the Province of Maniema. Thus, this study mainly aims to determine the characteristics of these four varieties as well as their variations according to species and seasons. To achieve this objective, these varieties were evaluated on the basis of morphological and agronomic descriptors relating to vegetative parameters, in particular the height or length of the plants, the diameter at the collar of the plants, the leaf area, the number of nodules, etc. The data collected were subjected to statistical analyses for possible differences between the varieties studied as well as between the two seasons observed. The results obtained showed significant morphological variability between the varieties observed. Some varieties showed more vigorous vegetative growth (high height and diameter for VITA7) and greater leaf development (high surface area for H4). This morphological diversity reflects the existence of an exploitable genetic potential for varietal improvement and adaptation of cowpea to local agro-ecological conditions.